ROLE OF LIQUIDITY AND PROFITABILITY OF SHARIA BANK ON INDONESIAN ECONOMIC GROWTH - Iwan Setiawan; Teti Sofia Yanti (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2021)
This research aims to find out the factors that determine liquidity and profitability as well as the contribution of Sharia banking to the economic growth in Indonesia. The study used quarterly data for the period 2009-2019, a multiple regression model with the Ordinary Least Square (OLS) analysis method. The results revealed that capital, financing and third party funds are factors that determine the liquidity of Sharia banking. Sharia banking profitability is influenced by capital and inflation. The role of Sharia banking on economic growth occurs through financing activities, large capital and utilization of Sharia monetary policy instruments. Efforts to control liquidity at optimal levels can be done by taking into account the capital factors held by Sharia banking. Efforts to achieve maximum value of profitability can be implemented by benefiting price stability in the macroeconomic. Efforts to boost economic growth are carried out by utilizing rising prices and limiting the profit value of Sharia monetary policy instruments. Moreover,  Sharia banking is able to increase the share of financing channeled.